Relationship between risky sexual behaviors and family functioning in students aged 14 to 19 from public and private institutions in Lima - Quiroz Muñoz, Analy (2022)
Objective: to determine the relationship between risky sexual behaviors and family functioning in students aged 14 to 19 from public and private institutions in Lima. Methodology: quantitative approach, non-experimental design, correlational and cross-sectional type since the variables are not manipulated. In data collection, the Sexual Behavior Questionnaire and the Family Functioning Perception Test (FFSIL) (designed by Pérez, Cuesta, Louro and Bayarre in 1997) were applied. The population was made up of 201 students from the 3rd, 4th and 5th grades of the secondary level. Results: In the first variable, the significant percentages in family dynamics are 34.3% and 36.8% in “Moderately functional” and “Functional”, respectively, with a “Adequate” family environment mostly perceived; likewise, in the second variable, 28.4% indicate that they are sexually active, being the age of 12 years the earliest in sexual initiation. Finally, in the association between both variables, a significant correlation is obtained between Family functioning and Group sexual relations (p <0.05, p = .004), however, a negative relationship is perceived between the other risky sexual behaviors and family functioning. Conclusion: There is a negative relationship between risky sexual behaviors and family functioning, however, a positive relationship was found between sexual behavior “group sex” and family functioning.